DIE SA WEERMAG EN BEWARING - Militaria, Editorial Team (Scientia Militaria - South African Journal of Military Studies, 2012)
Watch an old building with anxious care, guard it as best you may, and at any cost, from any influence of dilapidation. Count it’s stones as you would the jewels in a crown. Set watchers about, as if at the gates of a besieged city. Bind it together with iron when it loosens, stay it with timber when it declines and do this tenderly and reverently and continually and a generation will be born and pass away beneath its shadow - John Ruskin.